Pracownicy książki w Akademii Połockiej (1812–1820) - Kadulska, Irena (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The paper presents activities of the printing house founded in 1787 at the Jesuit College in Polotsk. The printing house became an academic printing house in 1812; it ceased to exist at the time of the dissolution of the Academy. The group of the most important printing house personnel, including the managing prefects and the employees directly associated with books – from the censors and the coadjutors to the printing house boys, is listed. Based on the existing inventory lists, their workshop, i.e. the printing equipment housed in all the printing house rooms, can be presented in detail, and their printing achievements, i.e. editions of the books stored in the warehouses and the academic bookshop, can be indicated.